1986
DOI: 10.1177/00220345860650010901
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Studies on the Anti-inflammatory Action of Phenolic Compounds

Abstract: The mechanism of the anti-inflammatory action of phenolic compounds was examined using neutrophil chemotaxis. Chemotactic activity of guinea pig peritoneal neutrophils to N-formylmethionyl-leucylphenylalanine (FMLP) was suppressed in a concentration-dependent manner. The order of drug potency in inhibiting the neutrophil chemotaxis was eugenol much greater than thymol greater than guaiacol much greater than phenol. The concentrations of phenolic compounds used in these experiments did not induce lactate dehydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
31
0
2

Year Published

1989
1989
2013
2013

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(35 citation statements)
references
References 13 publications
2
31
0
2
Order By: Relevance
“…The same is true of thymol (López Malo et al, 2005;Kim & Lee, 2004), which in addition has anti-inflammatory (Azuma et al, 1986) and antispasmodic (Astudillo et al, 2004) activities. The possibility that some artificial antioxidants (BHT, BHA) employed in the food and cosmetics industries to prevent the oxidation of fats and oils might have toxic effects, together with consumers' preference for natural products, has promoted research into many natural antioxidants, among them the essential oils of spices (Cuvelier et al, 1996).…”
Section: Introductionmentioning
confidence: 81%
“…The same is true of thymol (López Malo et al, 2005;Kim & Lee, 2004), which in addition has anti-inflammatory (Azuma et al, 1986) and antispasmodic (Astudillo et al, 2004) activities. The possibility that some artificial antioxidants (BHT, BHA) employed in the food and cosmetics industries to prevent the oxidation of fats and oils might have toxic effects, together with consumers' preference for natural products, has promoted research into many natural antioxidants, among them the essential oils of spices (Cuvelier et al, 1996).…”
Section: Introductionmentioning
confidence: 81%
“…The positive effect of dietary essential oils on sow health and production may be because of the effects of antioxidant (Aeschbach et al, 1994), antibacterial (Didry et al, 1994), antiphlogistic (Azuma et al, 1986), and antiinfl ammatory (Azuma et al, 1986) effects. Khajarern and Khajarern (2002) stated that carvacrol and thymol affected the mucosal membrane in the intestines and accelerated the renewal rate of enterocytes on the surface intestinal villi; this would reduce pathogen attachment to enterocytes and improve nutrient absorption capacity.…”
Section: Discussionmentioning
confidence: 99%
“…It Significantly different from the control by Student's t-test, P<0.05. has been suggested that the anti-inflammatory activity of some drugs may be partly due to their ability to interfere with radical-mediated reactions. Azuma et al (8) reported that phenolic compounds inhibited neutrophil chemotaxis. They suggested that the preven tion of the production of oxygen free-radicals by inhibiting leukocyte chemotaxis with phenolic compounds is one mechanism of the anti-inflammatory action of such com pounds.…”
mentioning
confidence: 99%